Mediation Effect of Trust on the Success Gofood Partners in Utilizing Gobiz Application - Bayu Prabu (Sistemasi: Jurnal Sistem Informasi, 2022)
Changes in the shopping behavior of consumers who like to shop online and the rapid development of technology require micro, small, and medium enterprises (MSMEs) especially culinary entrepreneurs to find ways to utilize easy-to-use technology as an online marketing system, namely by becoming a Gofood partner and using Gobiz application. This study aimed to test the trust of Gofood partners in utilizing Gobiz application as an online marketing medium through an assessment of the success information system of DeLone & McLean model. The population in this study was MSMEs culinary in JABODETABEK. The sample of this study was taken using a non-probability sampling method with a purposive sampling approach with the consideration that sample was selected based on the research objectives, namely MSMEs used Gofood and utilize Gobiz application in their business activities. The sample size used was 200 Gobiz application users. The analytical technique used in this study was structural equation model (SEM) analysis with help of smartPLS 3 software. The results of this study indicated trust of Gofood partners can be influenced by information quality, system quality, and service quality from Gobiz application, then trust also has a direct effect on user satisfaction and net benefits by Gofood partners, and trust can also mediate information quality and system quality on user satisfaction and net benefits by Gofood partners. So the results of this study can provide empirical support trust can be combined with the Delone& McLean model on the success of Gofood partners in utilizing the Gobiz application in JABODETABEK.